BS ISO/IEC 14543-5-104. Information technology. Home Electronic System (HES) architecture. Part 5-104. Intelligent grouping and resource sharing for HES Class 2 and Class 3. RA server-based smart lock application (9th July 2021) - British Standards Institution,
No abstract available